PELAKSANAAN METODE BERMAIN PERAN PADA ANAK USIA 5-6 TAHUN - Mulyati, Indah; Yuniarni, Desni; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The general problem in this research is "How is the implementation of role playing method in children aged 5-6 years Kindergarten Kemala Bhayangkari XIII Pontianak?." The method used is descriptive method with qualitative approach. Technique of collecting data in this research is observation, interview, field note and documentation study. Based on the results of data analysis showed that the implementation of role playing methods in children aged 5-6 years in Kemala Bhayangkari XIII Pontianak kindergarten is in accordance with the theory.        Keywords: Play Child Role. Kindergarten Students